Greek Warrior Helmet Facies (Wolf-hirschhorn Syndrome) - Biswas, P; Choudhury, R; Gayen, S; Guha, D; Roy, S; Dasgupta, MK (Journal of Nepal Paediatric Society, 2015)
Wolf-Hirschhorn syndrome (WHS) is caused by a chromosomal deletion of the band 4p16.3 with characteristic craniofacial features -’Greek warrior helmet’5 facies (prominent glabella, hypertelorism, broad beaked nose and frontal bossing), high-arched eyebrows, protruding eyes, epicanthal folds, short philtrum, distinct mouth with downturned corners, micrognathia, dysplastic ears, preauricular tags. Till date there are very few case reports of Wolf-Hirschhorn syndrome.Here we report a case that had characteristic dysmorphic facies (Figure 1) ‘Greek warrior helmet’ and was diagnosed as a case of WHS. But presence of Meningo-encephalocele and lissencephaly is rarely reported in literature in association with Wolf-hirschhorn syndrome till date. J Nepal Paediatr Soc 2014;34(3):239-243 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10289